2021
DOI: 10.1136/thoraxjnl-2021-216964
|View full text |Cite
|
Sign up to set email alerts
|

Burden of nosocomial COVID-19 in Wales: results from a multicentre retrospective observational study of 2508 hospitalised adults

Abstract: The burden of nosocomial SARS-CoV-2 infection remains poorly defined. We report on the outcomes of 2508 adults with molecularly-confirmed SARS-CoV-2 admitted across 18 major hospitals, representing over 60% of those hospitalised across Wales between 1 March and 1 July 2020. Inpatient mortality for nosocomial infection ranged from 38% to 42%, consistently higher than participants with community-acquired infection (31%–35%) across a range of case definitions. Those with hospital-acquired infection were older and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 11 publications
3
36
1
2
Order By: Relevance
“…The impacts of healthcare-associated COVID-19 on the prognosis of patients were significantly more critical than those for HCWs and companions, especially in wards caring for vulnerable groups [ 15 , 16 ]. The 30-day mortality of the patients in this study was approximately 40%, which is similar to the rates reported in other studies [ 2 , 3 ]. Aging is a known risk factor for mortality in patients with COVID-19 [ 15 , 17 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The impacts of healthcare-associated COVID-19 on the prognosis of patients were significantly more critical than those for HCWs and companions, especially in wards caring for vulnerable groups [ 15 , 16 ]. The 30-day mortality of the patients in this study was approximately 40%, which is similar to the rates reported in other studies [ 2 , 3 ]. Aging is a known risk factor for mortality in patients with COVID-19 [ 15 , 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…During the coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), healthcare-associated transmission has emerged as a significant concern worldwide, accounting for up to 40% of all confirmed COVID-19 cases according to early reports [ 1 ]. Healthcare-associated COVID-19 outbreaks pose significant threats to both patients and healthcare workers (HCWs) [ [2] , [3] , [4] , [5] ] and place enormous pressure on the daily operation of healthcare systems. This underscores the importance of infection prevention and control (IPC) practices and mitigation measures to prevent healthcare-associated outbreaks and contain the spread of such outbreaks once they emerge in healthcare settings.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Kastora et al demonstrated a variable increase in mortality between single CFS increments [ 17 ]. In most of those studies reporting on CFS, categorization was arbitrary and the authors did not report outcomes for each CFS score except five included studies [ 43 , 50 , 52 , 69 , 71 ]. In contrast to recent meta-analyses, we sought to analyse the most meaningful arrangements of CFS groups dividing patients into a fit to minimal degree of frailty group compared to patients with more advanced level of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…We screened study quality through self-identified use of reporting standards. Three (14%) reports referenced the STrengthening the Reporting of OBservational studies in Epidemiology (STROBE) statement (9,12,24). Tables 2-4 show the formal risk of bias assessments.…”
Section: Risk Of Bias In Studiesmentioning
confidence: 99%
“…The UK COVID-19 Clinical Information Network (CO-CIN) estimated 31,070 nosocomial COVID-19 infections occurred in England between February and July 2020, but made no assessment of the risk of mortality (8). We recently reported our initial experience from the first wave of the COVID-19 pandemic across the nation of Wales, using data collected from 2508 hospitalised adults (9). In this observational study, inpatient mortality rates for nosocomial COVID-19 ranged from 38% to 42% and were consistently higher than participants with community-acquired infection (31% to 35%) across a range of possible case definitions.…”
Section: Introductionmentioning
confidence: 99%